2015
DOI: 10.1038/nature14332
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase 9A controls nitric-oxide-independent cGMP and hypertrophic heart disease

Abstract: Cyclic guanosine monophosphate (cGMP) is a second messenger molecule that transduces nitric oxide (NO) and natriuretic peptide (NP) coupled signaling, stimulating phosphorylation changes by protein kinase G (PKG). Enhancing cGMP synthesis or blocking its degradation by phosphodiesterase type 5A (PDE5A) protects against cardiovascular disease1,2. However, cGMP stimulation alone is limited by counter-adaptions including PDE upregulation3. Furthermore, though PDE5A regulates NO-generated cGMP4,5, NO-signaling is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
299
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 297 publications
(334 citation statements)
references
References 30 publications
14
299
2
2
Order By: Relevance
“…Western blot analysis was used to determine protein levels as previously described6, 16, 19, 24 in buffer containing 150 mmol/L NaCl, 10 mmol/L Tris pH 7.4, 1 mmol/L EDTA, 1% Triton X‐100, and protease/phosphatase inhibitors (Halt, Thermo Scientific). After sonication, the lysates were centrifuged at 17 000 g for 10 minutes to remove insoluble material and sample concentration was then determined by Bradford assay (Bio‐Rad).…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was used to determine protein levels as previously described6, 16, 19, 24 in buffer containing 150 mmol/L NaCl, 10 mmol/L Tris pH 7.4, 1 mmol/L EDTA, 1% Triton X‐100, and protease/phosphatase inhibitors (Halt, Thermo Scientific). After sonication, the lysates were centrifuged at 17 000 g for 10 minutes to remove insoluble material and sample concentration was then determined by Bradford assay (Bio‐Rad).…”
Section: Methodsmentioning
confidence: 99%
“…In another example, Hsa21-encoded PDE9a hydrolyses cGMP and is a major determinant of intracellular cGMP levels important for signalling cascades. PDE9a overexpression contributes to maladaptive hypertrophy and cardiac failure in humans and in a mouse model of aortic stenosis [143]. Conversely, expression of miR-99a correlates closely with cardiac function in mice, and overexpression of miR-99a attenuates both cardiomyocyte hypertrophy in vitro and aortic stenosis-associated cardiac hypertrophy in vivo [144].…”
Section: Congenital Heart Defects and Cardiovascular Disease In Down mentioning
confidence: 99%
“…The increase in ANP that occurs with cardiac hypertrophy might help compensate for the increase in afterload. In the past few years, studies have revealed that the antihypertrophic effect of ANP is mediated by the guanylylcyclase‐A receptor and cGMP production (Klaiber et al ., 2011; Lee et al ., 2015). Furthermore, ANP has been used to reduce cardiac remodeling after myocardial infarction (Kuga et al ., 2003).…”
Section: Discussionmentioning
confidence: 99%